Brotherly love: freemasonry and male friendship in Enlightenment France - Loiselle, Kenneth (Cornell Univ. Press, 2014)
The masonic utopia of friendship -- Friendship in ritual -- Confronting the specter of sodomy -- "New but true friends" : the friendship network of Philippe-Valentin Bertin du Rocheret -- Friendship in the age of sensibility -- Friendship under fire : freemasonry in the French Revolution